MENANAMKAN NILAI BUDI PEKERTI MELALUI PROGRAM ADIWIYATA DI SD : BELAJAR DARI SDN JAJAR TUNGGAL III/452 WIYUNG - Tasi'awati Salsa Kaliwanovia; Nanda Fatimah Tul Zahro; Ahmad Dani Saputra; Wenus Kogoya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the Adiwiyata Program in instilling character values among elementary school students at SDN Jajar Tunggal III/452 Wiyung. The research employed a descriptive qualitative approach with a field research design. Data were collected through observations, interviews, questionnaires, and documentation. The findings indicate that the Adiwiyata Program plays a role in fostering students’ character values, particularly discipline, responsibility, cooperation, environmental awareness, and honesty. These values are cultivated through daily school activities, environment-based learning, and exemplary behavior demonstrated by teachers. The Adiwiyata Program not only contributes to creating a clean and healthy school environment but also supports the sustainable development of students’ character from an early age.